Exploration of Gravel Roads Erosion Data in Uganda - Semwogerere, Twaibu; Lating, Peter Okidi; Kucel, Samuel Baker (Intl. Conf. On Advances in Computing, Electronics and Electrical Technology, 2015)
The main objective for this study was to explore the erosion data from across Uganda gravel roads. Gravel/dirt/rural roads constitute a larger part of the total road networks in developing countries and are top-listed for accumulation of wealth for such countries like Uganda. Generally, quantitative methods through experimental designs were used. Data was generated from various experiments and STATA output and used in the analysis and exploration. They include among others sieve analysis, measurement of road rill/dune sizes, Atterberg tests, and dry-density tests. These were conducted to reflect the characteristics of road subgrades and sediments from these roads. A brief comparison of one of the original erosion models, USLE/RUSLE was done with the erosion model developed for the maintenance of gravel roads, EMMOGR and conclusions reached.